(untitled) (Mustansiria Dental Journal, 2018)
Background Resorption of alveolar bone is the best recognized feature of mandibular aging in the edentate subject. The aim of this is study to evaluate the mandibular canal wall resorption using panoramic radiographs among edentulous male and female. Material and method The sample of this study was collected from patients who attended Teaching Hospital of the College of Dentistry at Al- Mustansiria University and panoramic radiographs were taken in Al-Karama specialized center for dentistry. Forty three patients were selected in this study with age range between 59-85 years (25 males and 18 females) . Panoramic radiographs for all patients and sides were examined and evaluated . Results Chi-square between males and females of angular cortical thickness (ACT) ≥ 1mm and ACT ˂ 1mm was (37.06) which statistically significant with p-value (0.008) and between resorption (grades) and age of males was(34.72) which it statistically significant p-value(0.049) also between resorption (grades) and age of females was(15.6) which was statistically significant p-value (0.003) . Sperman correlation showed statistically significant moderate correlation between gender and age (r=0.581,p-value=0.01) and there was a moderately statistical significant correlation between the grades of mandibular canal resorption and the angular cortical thickness measurements in both gender (r=0.532,p-value=0.033). Conclusion The resorption of the wall is found more often in edentulous females than in the males due to hormonal imbalance.